2019
DOI: 10.1186/s12903-019-0893-3
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral abscess following the self-extraction of teeth in patient with Ebstein’s anomaly: a case report

Abstract: Background Antibiotic prophylaxis before invasive treatments, including dental extractions, is still recommended for patients at high risk of infective endocarditis. However, the risk from self-extraction of teeth in daily life of patients with intellectual disabilities is uncertain. Case presentation A 6-year-old patient with Ebstein’s anomaly developed cerebral abscess, which appeared associated with infective endocarditis of dental origin. Two weeks after self-extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Studies have shown that in cyanotic congenital heart diseases with right to left shunt, such as tetralogy of Fallot or functional single ventricle, venous blood may enter directly into the systemic circulation, thereby increasing the risk for developing brain abscesses [ 6 , 7 ]. Given that the patient had a cyanotic congenital heart disease with right to left shunt, we speculated that the patient developed multiple brain abscesses caused by apical periodontitis of deciduous teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that in cyanotic congenital heart diseases with right to left shunt, such as tetralogy of Fallot or functional single ventricle, venous blood may enter directly into the systemic circulation, thereby increasing the risk for developing brain abscesses [ 6 , 7 ]. Given that the patient had a cyanotic congenital heart disease with right to left shunt, we speculated that the patient developed multiple brain abscesses caused by apical periodontitis of deciduous teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus viridans have been demonstrated to cause brain abscess in patients with infected pulp [11]. One descriptive and comparative metagenomic study showed how there was a 65.5% overlap between microorganism species of empyemas and brain abscesses, with Streptococcus intermedius, Fusobacterium nucleatum and Aggregatibacter aphrophilus being the most common pathogens [12].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of surgical procedures within the skull includes the possibility of introducing other pathogens, which may respond to different antibiotic treatments and require alternative subsequent management. Thus, the neurosurgical drainage approach is only added to the antibiotic treatment when there is sufficient size of tumor to use more than antibiotics, due to the risk the procedure itself can present [12,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation